Bilinear Grid Search Strategy Based Support Vector Machines Learning Method - Lin, L.; Xiaolong, Z.; Kai, Z.; Jun, L. (Informatica, 2014)
Bilinear Grid Search Strategy Based Support Vector Machines Learning Method